2021
DOI: 10.1002/emp2.12378
|View full text |Cite
|
Sign up to set email alerts
|

Crucial considerations: Sex differences in the epidemiology, diagnosis, treatment, and outcomes of acute pulmonary embolism in non‐pregnant adult patients

Abstract: Acute pulmonary embolism (PE) affects over 600,000 Americans per year and is a common diagnostic consideration among emergency department patients. Although there are well-documented differences in the diagnosis, treatment, and outcomes of cardiovascular conditions, such as ischemic heart disease and stroke, the influence of sex and gender on PE remains poorly understood. The overall age-adjusted incidence of PE is similar in women and men, but women have higher relative rates of PE during early and mid-adulth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 123 publications
1
12
0
1
Order By: Relevance
“…The incidence of pulmonary embolism increases with age in both sexes [ 10 , 11 , 14 , 15 ], with a relative risk (RR) of venous thromboembolism (VTE) that nearly triples between 60–69 years of age and at >80 years of age (RR: 5.983; 95%CI: 5.708–6.273; p = 0.0001) vs. RR: 14.890; 95%CI: 14.103–15.721; p = 0.0001). Although a review by Jarman et al reports a similar overall age-adjusted incidence of PE between the sexes, most observational studies and reviews in the literature have found men to have a higher overall age-adjusted incidence of PE compared to females [ 10 , 11 , 16 , 17 , 18 ], in a male:female sex ratio of 1.2:1 [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pulmonary embolism increases with age in both sexes [ 10 , 11 , 14 , 15 ], with a relative risk (RR) of venous thromboembolism (VTE) that nearly triples between 60–69 years of age and at >80 years of age (RR: 5.983; 95%CI: 5.708–6.273; p = 0.0001) vs. RR: 14.890; 95%CI: 14.103–15.721; p = 0.0001). Although a review by Jarman et al reports a similar overall age-adjusted incidence of PE between the sexes, most observational studies and reviews in the literature have found men to have a higher overall age-adjusted incidence of PE compared to females [ 10 , 11 , 16 , 17 , 18 ], in a male:female sex ratio of 1.2:1 [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite a higher age-adjusted incidence of PE in men, the patterns of developing PE vary with age among women and men [ 14 , 18 , 19 ]. Studies have suggested that women diagnosed with PE are more likely to be older than men [ 15 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that women had more severe symptoms such as low blood pressure (1.19 % vs. 1.04 %), more episodes of blood transfusions (6.49% vs. 4.47%), and were treated more with thrombolytics (27% vs. 23%) compared to men [17]. Also, a review study by Angela et al, showed that when given anticoagulants, women were 46% vs 21% more likely to suffer from bleeding problems than men [21] In addition, from our findings, the APACHE II severity scores were 24 and (OR; 1.07, 95%CI, p-0.03) which was found to be a predictor of death in non-survivors (Table 4). Corresponding to our findings, Ergan et al, retrospectively studied 56 patients, with 13% mortality also found APACHE II score >18 cut-offs to be a predictor of poor outcome and increased mortality risk, however, more deaths were recorded in males (32.1% vs. 69.2%; p=0.943) inversely co-related to our findings [11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential severity of acute PE, diagnosis can be challenging due to its nonspecific presentation. The most common presenting complaints among patients diagnosed with PE are chest pain and dyspnea, which are also among the five most common presenting complaints of all patients evaluated in U.S. EDs and account for over 10 million patient visits per year 5,6 . Precision in diagnostic testing is critical for avoiding missed PE diagnoses while simultaneously minimizing the harms associated with low‐value testing such as radiation exposure, 7,8 complications from iodinated contrast, 9,10 and harms associated with treatment of false‐positive and incidental findings 1,11–13 .…”
Section: Introductionmentioning
confidence: 99%